Retrospective cohort study of the association between maternal employment precarity and infant low birth weight in women in the USA - Anjum Hajat; Divya Patil; Daniel A Enquobahrie; Trevor Peckham; Noah Seixas (BMJ Open)
Objectives To investigate the association between maternal employment precarity and infant low birth weight (LBW), and to assess if this association differs by race/ethnicity.Methods Data were collected from 2871 women enrolled in the National Longitudinal Survey of Youth 1979 and the National Longitudinal Survey of Youth 1979 Children and Young Adult Cohort. Employment precarity was evaluated using a summary variable that combined several employment attributes: availability of employer-sponsored insurance, income, long shifts, non-daytime shifts, availability of employer sponsored training or educational benefits and membership in a union or collective bargaining unit. Employment precarity scores (a sum of the number of negative employment attributes) were categorised into low (0–2), medium (3) and high (4-6). LBW was defined as weight less than 2500 g at birth. Modified Poisson models were fit to calculate risk ratios and 95% CIs and adjusted for maternal age, race/ethnicity, educational attainment, nativity, prepregnancy body mass index, alcohol consumption, smoking during pregnancy and infant year of birth. We assessed effect modification by maternal race/ethnicity using a composite exposure-race variable.Results Women with high employment precarity had higher risk of a LBW delivery compared with women with low employment precarity (RR: 1.48, 95% CI: 1.11 to 1.98). Compared to non-Hispanic/non-black women with low employment precarity, non-Hispanic black women (RR: 2.68; 95% CI: 1.72 to 4.15), Hispanic women (RR: 2.53; 95% CI: 1.54 to 4.16) and non-Hispanic/non-black women (RR: 1.46; 95% CI: 0.98 to 2.16) with high employment precarity had higher risk of LBW.Conclusions We observed higher risk of LBW in pregnancies of women with high employment precarity; this association was stronger among black and Hispanic mothers compared to non-Hispanic/non-black women. Findings of this study can be used to inform antenatal care and identify workplace policies to better support women who work during pregnancy.